Esthetic Rehabilitation through Crown Lengthening Surgery and Conservative CAD/CAM Veneers: A Multidisciplinary Case Report - Leandro Passos; Fernando Peixoto Soares; Mauricio Gallo (Case Reports in Dentistry)
This case report describes a successful multidisciplinary approach used to improve the smile esthetics of a patient presenting with excessive gingival display, asymmetric gingival margins, and small upper anterior teeth and lower anterior teeth. The treatment combined esthetic crown lengthening, dental bleaching, and restorative dentistry using CAD/CAM veneer. The 6-month follow-up examination confirmed the stability of the modification and absence of adverse effects.